The Distributions of Iron Average Charge States in Small Flux Ropes in Interplanetary Space: Clues to Their Twisted Structures. Issue 9 (8th September 2018) - Huang, Jia; Liu, Yong C.‐M.; Peng, Jun; Qi, Zhaohui; Li, Hui; Klecker, Berndt; Song, Hongqiang; Zheng, Jinlei; Hu, Qiang
Abstract: Small flux ropes (SFRs) have been studied for decades, but their source regions and formation mechanisms are still under debate. In this study, we focus on the formation mechanism of the twisted structures of SFRs. Current research on magnetic clouds suggests five‐type distributions of the time structure of iron average charge states ( Q ), which imply different formation mechanisms of twisted structures. We use a similar method to identify the Q types of 25 SFRs. However, only four of these five types of distributions are found among these SFRs. Because different origins of SFRs are characteristically affecting the formation of Q types, the possible source regions of these SFRs are distinguished. With additional compositional parameters, SFRs are reconfirmed to originate from two types of source regions: the solar corona and the interplanetary medium. Based on these results, our analysis indicates that the twisted structures of SFRs originating from the solar corona may be formed predominately during eruptions. SFRs originating from interplanetary space are related to complex magnetic reconnection processes, which may result in intricate Q distributions due to the reconstruction of magnetic field topology. Key Points: The small flux ropes have been categorized into four types considering the characteristics of the iron charge states Small flux ropes may have their twisted structures formed predominately during their eruption processes Small flux ropes are reconfirmed to have two source regions